Redistributed versus homogenous radiotherapy dose for head and neck cancer; a treatment planning study. (July 2017) - Heukelom, Jolien; Lamers, Emmy; Slooten, Erik; van Werkhoven, Erik; Rasch, Coen; Sonke, Jan-Jakob
Abstract: Dose redistribution, where radio-resistant parts of the tumour are boosted while the border of the planning target volume receives a lower dose has the potential to increase local control in advanced head and neck squamous cell carcinoma (HNSCC). In this treatment planning study for 20 patients, standard radiotherapy (RT) of 70 Gy, was compared to redistributed RT following the ARTFORCE trial protocol (NCT01504815), i.e., a fluorodeoxyglucose-positron emission tomography (FDG-PET) based heterogeneous simultaneous-integrated-boost to a total dose of 64–84 Gy. Redistribution marginally increased the mean ipsilateral ⧹contralateral parotid dose by 1.55⧹0.55 Gy but not dose to other organs at risk.